Germs, Guns, and Fear in Disaster Response: A Rapid Qualitative Assessment to Understand Fear-Based Responses in the Population at Large: Lessons From Sierra Leone 2014-2015. (14th March 2023) - Nally, Cora P.; Van de Voorde, Patrick; Temmerman, Marleen; Adam, Mary
Abstract: We set out to assess the feasibility of community-focused randomized qualitative assessment at the start of an emergency to identify the root causes of fear-based responses driving the pandemic. We used key informant interviews, focus group discussions, reviewing of government and non-government organization documents, combined with direct field observation. Data were recorded and analyzed for key-themes: (1) lack of evidence-based information about Ebola; (2) lack of support to quarantined families; (3) culturally imbedded practices of caring for ill family members; (4) strong feeling that the government would not help them, and the communities needed to help themselves: (5) distrust of nongovernmental organizations and Ebola treatment centers that the communities viewed as opportunistic. On-the-ground real-time engagement with stakeholders provided deep insight into fear-based-responses during the Ebola epidemic, formed a coherent understanding of how they drove the epidemic, presenting an alternative to the standard disaster-response United Nations-strategy, producing community-driven solutions with local ownership.